The Boston Consulting Group's strategic menagerie - C. G. Robinson (South African Journal of Business Management, 1985)
In this, the first in a series of three articles which summarize the Boston Consulting Group's approach to setting strategy, problems of funding growth and allocating resources around a portfolio of products or strategic business units are highlighted. The relationships between the stage of the product life cycle, the funding requirements of a business, and the alternatives for generating funds are explored. Growth and risk Issues are highlighted and the maximum sustainable rate of growth from internally generated sources is derived. The impact of the experience curve on capital structure, production costs, and competitive position emphasizes the interaction between life cycle position, cost position, profitability, and cash flow. This logically leads to the Boston Consulting Group's Growth Share Matrix as a basis for resource allocation around a portfolio of businesses. Optimum cash flow and investment criteria are arrived at.
Keywords: 650